Performance of microscopy and rapid test for the diagnosis of mixed malaria in an endemic area of Colombia (2025)
Background: Mixed infection by Plasmodium (MIP) occurs when more than one species are infecting one individual at the same time. Methods: Frequency of MIP was determined in a cohort of patients with acute febrile syndrome. Diagnostic performance of microscopy (MI) and a rapid diagnostic test (RDT) was evaluated against real-time PCR (qPCR), as reference method. Results: The frequency of MIP was 3% by qPCR, 1.4% by MI and 0.4% by RDT. The sensitivity of MI and RDT for detecting MIP was 21.43% and 15.25%, respectively, and specificity was over 99% for both techniques. Conclusion: The currently available tests for the diagnosis of Plasmodium in the field, showed poor performance for detecting MIP in this study. It is necessary to improve diagnostic tests sensitivity for the correct detection of these coinfections and to monitor the elimination of parasitemia to detect possible recurrences due to inadequate treatments.